The degree to which logical thinking skills are included in national education books for grades (eighth, ninth and tenth) for the basic stage in Jordan - Basyouni, Zahia Mansour Basheer (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the degree of inclusion of logical thinking skills in the national education books in Jordan, by analyzing the content of these books and the study used the descriptive approach. The tool was to build a list of logical thinking skills, which included five skills, It was applied to a sample of national education books, they numbered (three books). With the statistical treatment of data, the results of the study revealed the availability of logical thinking skills in varying degrees in the national education books for grades (eighth, ninth and tenth) for the basic stage in Jordan, where the skill (conclusion) came at a high rate, and the skill (disclosure of fallacies) came at an average rate, The other skills came in low proportions in a row (comparison, arrangement, classification), and the results showed that the national education book for the ninth grade has occupied the first rank in the total number of iterations (434) repetitively, as the share of the ninth basic book reached (154) repetitions, and After him came the eighth book Asa C as it reached (142) repetitions, and came in the third and final rank of the tenth grade basic book as it reached (138) repetitions, and the study recommended conducting more studies to identify the logical thinking skills in books and other academic stages.